2019
DOI: 10.1002/bjs.11246
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in a randomized trial of neoadjuvant chemotherapy or chemoradiotherapy plus surgery in patients with oesophageal cancer (NeoRes trial)

Abstract: Background: There are few data comparing health-related quality of life (HRQoL) after neoadjuvant chemotherapy alone (nCT) compared with neoadjuvant chemoradiotherapy (nCRT) in patients with oesophageal cancer.Methods: In the NeoRes trial, patients were assigned randomly in a 1 : 1 ratio to receive either cisplatin 100 mg/m 2 on day 1 and an infusion of 750 mg per m 2 5-fluorouracil over 24 h on days 1-5 in three 21-day cycles (nCT) or the same chemotherapy regimen, but with the addition of 40 Gy radiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Despite multidisciplinary advances in EC treatment, surgery is still the curative strategy of choice. However, neoadjuvant chemotherapy (nCT) or neoadjuvant chemoradiotherapy (nCRT) followed by surgery has been shown to achieve a better outcome for patients with EC compared with surgery alone ( 5 , 6 ), and is related to improvements in overall survival and disease-free survival. Notably, 15–30% of all patients with EC treated with nCRT followed by surgery achieve a pathological complete response (pCR) ( 7 9 ) and ~45% of patients with ESCC achieve pCR ( 7 , 10 , 11 ), where pCR is defined as no histological evidence of the tumor in the surgical specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Despite multidisciplinary advances in EC treatment, surgery is still the curative strategy of choice. However, neoadjuvant chemotherapy (nCT) or neoadjuvant chemoradiotherapy (nCRT) followed by surgery has been shown to achieve a better outcome for patients with EC compared with surgery alone ( 5 , 6 ), and is related to improvements in overall survival and disease-free survival. Notably, 15–30% of all patients with EC treated with nCRT followed by surgery achieve a pathological complete response (pCR) ( 7 9 ) and ~45% of patients with ESCC achieve pCR ( 7 , 10 , 11 ), where pCR is defined as no histological evidence of the tumor in the surgical specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Patients treated with NAC were signi cantly associated with a lower preoperative SMI and BMI (Table 3) and had a signi cantly lower preoperative SMI compared with patients who did not receive NAC (Figure 3). NAC reduced skeletal muscle mass by approximately 3% because of side effects, such as fatigue, loss of appetite, and decreased exercise tolerance accompanied by thrombocytopenia [31][32][33][34][35]. It has also been revealed that patients with a low preoperative SMI have less marked loss of SMI after esophagectomy [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, direct comparisons of these two approaches do not show a consistent benefit for one over the other [ 10 ] and complication rates may be higher following nCRT [ 9 ]. There are few published reports with patient-reported outcome (PRO) data from randomized neoadjuvant therapy trials, representing a gap in our understanding of the impact of neoadjuvant therapy [ 11 ]. Recent trials have focused on identifying suitable candidates for neoadjuvant therapy regimens, involving chemotherapy or CRT.…”
Section: Introductionmentioning
confidence: 99%